New two dimensional liquid-phase colorimetric assay based on old iodine-starch complexation for the naked-eye quantitative detection of analytes. - Nie, J; Brown, T; Zhang, Y (Royal Society of Chemistry, 2016)
A new type of quantitative point-of-care liquid-phase colorimetric assay (LPCA) termed as two dimensional (2D) LPCA is designed using old iodine-starch complexation reaction firstly discovered in 1814. The naked-eye 2D LPCA's utility is well demonstrated with the simple, low-cost, portable detection and quantification of model analytes in buffer and/or human serum samples without the use of external electronic readers.